Radiation beam scanning for leaky wave antenna by using slots - Jamal S. Kasim; M.S. M. Isa; Z. Zakaria; M. I. Hussein; Mowafak K. Mohsen (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper provides an insight of a new, microstrip leaky wave antenna. It holds the ability to continue steer its beam at a swapping frequency. This is done with acceptable impedance matching while scanning and very little gain variation. Investigation is carried out on LWAs’ control radiation pattern in steps at a band frequency via vertical and horizontal slots. The enhancement is realized by etching horizontal and vertical slots on the radiation element. This study also presents a novel half-width microstrip leaky wave antenna (LWA). The antenna is made up of the following basic structures group’s vertical and horizontal slots. The reactance profile at the microstrip’s free edge and thus the main beam direction is changed once the control-cell states are changed. The radiation pattern direction changes by sweeping the operating frequency between 4 GHz to 6 GHz.The main beam may be directed by the antenna between 15o and 55o. C band achieved the measured peak gain of the antenna of 10 dBi at 4.3 GHz beam scanning range.